LESSONS LEARNED FROM EARLY IMPLEMENTATION STAGE OF ACCRUAL ACCOUNTING IN INDONESIA LOCAL GOVERNMENT A Case Study in Province XYZ - Irwan Taufiq Ritonga, Ritonga (2015)
Abstract Starting from 1 January 2015, all local governments in Indonesia implement accrual accounting. There is a big question as how good the implementation. Therefore, the objective of this study is to assess the implementation of accrual accounting in a local government in Indonesia for the first the month. This study utilizes descriptive-qualitative research method.